KAJIAN JEMBATAN KECAMATAN SENDANG (RUAS JALAN TUGU – PABYONGAN) KABUPATEN TULUNGAGUNG DENGAN METODE KOMPOSIT - Tri Yuli Purnomo; Lucia Desti Krisnawati; Yosef Cahyo Setianto Purnomo (Kadiri University, 2018)
Population growth in Tulungagung Regency, which is getting faster, must be balanced with adequate transportation infrastructure. Improvement of transportation facilities and infrastructure is in the form of bridge construction. In order to achieve good and truly mature planning, a careful feasibility study is required. From the results of research on the Sendang Bridge (Tugu - Pabyongan Road Section), the greatest force acting on the bridge includes: ultimate moment of support = 34.7 kNm and the ultimate moment of field = 23.8 kN, dead load = 101.12 kNm , live load = 11.09 kN / m, load 'D' = 304.73 kNm, load 'T' = 130 kN, brake load = 45.93 kNm, wind load = 14.70 kNm, earthquake load = 1, 1 kN / m. From the existing loading, a bridge plate with a thickness of 0.2 m is determined. The controls used were deflection requirements d <Ls / 240. 0.0313 <10.8 / 240 → OK, control voltage kip f = 16.77 Mpa. The girder profile is used WF 400.200.8.13. By calculating the structural load and the force acting on the bridge, the use of girder profile is safe to accept stress and deflection due to the forces on the upper structure.Pertumbuhan penduduk di Kabupaten Tulungagung yang semakin pesat harus diimbangi dengan sarana prasarana transportasi yang memadai. Peningkatan sarana dan prasarana transportasi ini berupa pembangunan jembatan. Untuk mencapai perencanaan yang baik dan benar-benar matang maka diperlukan studi kelayakan yang teliti. Dari hasil penelitian pada Jembatan Sendang (Ruas Jalan Tugu – Pabyongan) dihasilkan Gaya yang terbesar yang bekerja pada jembatan meliputi : momen ultimite tumpuan sebesar = 34,7 kNm dan momen lapangan ultimit sebesar = 23,8 kN, beban mati = 101,12 kNm ,beban hidup = 11,09 kN/m, beban ‘D’ = 304,73 kNm, beban ‘T’ = 130 kN, beban rem = 45,93 kNm, beban angin = 14,70 kNm, beban gempa =1,1 kN/m. Dari pembebanan yang ada ditentukan Plat jembatan setebal 0,2 m. Kontrol – kontrol yang di gunakan syarat lendutan d < Ls/240. 0,0313< 10,8/240 →OK , kontrol tegangan kip f = 16,77 Mpa. Profil gelagar digunakan WF 400.200.8.13 , dengan perhitungan beban struktur dan gaya yang bekerja pada jembatan, penggunaan profil gelagar tersebut aman menerima tegangan dan lendutan akibat gaya-gaya pada struktur atas.